SOUTHERN STRATEGY (Tufts Archival Research Center, 2007)
Document outlining the plan to get support from southern senators and congressmen in opposition to the issue of raising tobacco taxes to fund healthcare. Claims that doing so would financially devastate the south. Contains a three phase strategy with regard to visiting constituents and labor related issues, as well as a summary of the types of mass media to be used in the effort.